Caricature in Palestinian very Short Stories Written by Diasporic Writers - khoury, samah (International Journal of Language and Literary Studies, 2021)
This article studies the caricature techniques used in Palestinian very short stories written by writers living in the diaspora. This study includes three examples of very short stories in which caricature is manifested in events, characters and language. This technique is used in order to try to find the link between the harsh reality of post-1948 war and the changes it created, and the effects it had on society, politics and economics. I monitored the subjects that Palestinian authors write about in very short stories, and intend to expose the varied use of caricature in its different techniques. This study reveals how caricature is used in very short stories to expose the inhumane conditions, worsening relationships between human beings, and the way people turn to violence in an attempt to solve their problems. This violence surrounds people from all sides and defines their relationships, whether with other people, their leaders or their enemies.